Researching online for dummies - Basch, Reva (IDG Books Worldwide, 1998)
Includes index.; This book helps develop a multitiered research strategy using keywords and index terms to dive deep into the sources found on the Web.... Explore the mental tools and online resources successful researchers rely on every day, Take a look at the online world that goes beyond the Internet, Familiarize yourself with search engines, indexes, quick reference aids, and other online professional services you can access from your computer,See how Boolean searching and other power-search tips and techniques can greatly aid your research. Researching Online For Dummies, 2nd Edition, also offers a 30-page directory dedicated to describing selected research sites, services, and other useful online resources. The book's bonus CD-ROM includes search engine help files from Northern Light and Lycos as well as demo versions of Copernic, BullsEye, and WebWhacker